Structural, optical, electrical, dielectric, molecular vibrational and magnetic properties of La3+ doped Mg–Cd–Cu ferrites prepared by Co-precipitation technique. Issue 10 (15th May 2022) - Arshad, Muhammad Imran; Hasan, M.S.; Rehman, Atta Ur; Akhtar, Maria; Tung, Le Duc; Amin, N.; Mahmood, Khalid; Ali, Adnan; Trakoolwilaiwan, Thithawat; Thanh, Nguyen Thi Kim
Abstract: Ferrites are among the most frequently investigated materials mainly due to interesting and practically different properties. Therefore, easily and cost-effective lanthanum doped Mg0.5 Cd0.25 Cu0.25 Fe2-x Lax O4 (x = 0.0, 0.0125, 0.025, 0.0375 and 0.05) ferrites were synthesized by a co-precipitation route, a comprehensive characterisation of their structural, optical, electric, dielectric, molecular vibrational, and magnetic properties were carried out. X-ray diffraction analysis confirmed the formation of a cubic spinel structure. Variations in frequency bands were also observed with amplification in optical band gap energy (2.95 – 3.38 eV) due to La 3+ ions insertion. The electric resistivity had opposite trends at low and high temperatures with increasing La 3+ content. The Curie temperature, activation energy, and drift mobility were also determined to have values consistent with the semiconducting behavior of the soft ferrites. The saturation magnetization (MS ) has a maximum value 49.385 emu/g with remanent magnetization (Mr ) was 34.928 emu/g and coercivity 661.4 Oe for La 3+ concentration x = 0.05. The minimum dielectric loss was observed for La 3+ concentration x = 0.025. Moreover, the resistivity (ρ) has a maximum value of 7.95 × 10 4 Ω cm for La 3+ concentration x = 0.025. The calculated frequency range of La 3+ doped Mg–Cd–Cu ferrites was detected in the microwave range (3.36 – 10.80 GHz), suggesting the potential application of the materials in longitudinal recording media and microwave absorbance. Graphical abstract: Image 1 Highlights: La 3+ doped Mg–Cd–Cu ferritessamples synthesized via co-precipitation. The lattice constant increased with La 3+ substitution. At 303 K, for La 3+ concentration x = 0.025, maximum resistivity was observed. Magnetization saturation was increased with La 3+ concentration.